ENTREPRENEURSHIP IN LATIN AMERICA DURING THE 21st CENTURY - Muro, Cristina Tapia; Sanchez, Jorge Ricardo Vasquez; Castell, Fernando Figueroa (European Scientific Journal, ESJ, 2014)
This paper aims to provide an brief overview of Entrepreneurship during the last decade in three of the most representative economies of Latin America. With this objective, the relationship of different variables that pertain to both entrepreneurship and the elements that, according to the literature, are individual-level determinants of it (such as attitude, social norms and the perceived ability to develop individual action itself) are explored over time. The period analyzed is 2001-2012 for the cases of Brazil, Argentina and Mexico with indicators from the Global Entrepreneurship Monitor (GEM). The data show that for all selected countries, the perceived desirability, specifically the dimension of the social value given to the entrepreneurial activity, is positively and significantly associated with both the initiation of new business and the intent to undertake them. Looking at each country in particular, this important association persisted with at least one dimension of entrepreneurship (either the activity or the intention). The variable on perceived feasibility for conducting business is more strongly associated with entrepreneurship in the case of Brazil, in contrast to the cases of Argentina and Mexico where it, in general, does not reflect statistical significance.